A Study on the Dynamic Situation Response Scenario for Constructing ICT Convergence Disaster Response System - Lee, Chul-Gyoo; Moon, Sang-Ho; Yu, Young-Jung (International Journal of Engineering and Technology, 2019)
Recently, natural disasters due to changes in the natural environment such as climate change have appeared in various forms. In addition, due to the development of architectural technology, the construction of super high-rise buildings as well as the enlargement and complexation of buildings are rapidly taking place. Also, with the rapid increase in the population of the city due to industrialization, buildings are becoming larger and more complex. These natural and technological changes increase the possibility of a complex type of disasterâ€”either natural or social type of disaster, or a combination of both These changes strongly require the paradigm shift of response systems, including the prediction, preparation, response, and recovery phases of disasters. If social disasters such as fires occur in high-rise or large-scale buildings, not only large-scale casualties but also social losses could be expected to occur. Therefore, in the event of a major disaster such as earthquake, typhoon or tsunami, it is necessary to utilize response scenarios that can cope with various changes appropriately in disaster situations. In order to change the paradigm of the disaster response system, the proponents of this study identified the necessary functions and requirements for the transition to a dynamic situation response system. To do this, a case study was conducted on the disaster response system of super high-rise buildings and accident cases. These functions and requirements were aimed to be implemented in disaster response systems based on dynamic situation response scenarios. The system also included real-time information gathering, analysis, decision and action planning through the use of ICT technology. The scenarios were analyzed by task according to the specific situation corresponding to time, and then a strategy was designed to be applied to computerization, automation and intelligence. To verify dynamic situational response scenarios, the proponents confirmed the feasibility of the study by designing a database of the disaster response system which implements the scenario.Â